Determination of Auspicious Days in Wedding Traditions in Mandar, West Sulawesi: Perspective of Islamic Law - Sadat, Anwar; Tahmid Nur, Muhammad; Sadik, M.; Baharuddin, A. Zamakhsyari (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Determination of auspicious days is a discourse that still causes polemics and is often considered to be contrary to Islamic law. This study aims to discuss the determination of auspicious days in the Mandar wedding traditions in the context of Islamic law. This empirical legal study used a multiapproach framework that included the theory of social change and the theory of Islamic law, especially al-'urf (social tradition) and al-maslahah (public interest). Data were collected by means of in-depth interviews and literature reviews of scientific articles, textbooks, and books on Islamic law. The data were then analyzed through data display using the aforementioned theories. The results of the study revealed that determining auspicious days, practiced by the majority of the Mandar people prior to organizing a marriage, has been considered a custom and in accordance with Islamic law. Further, the Qur’an and hadith, as the sources of Islamic law, have also indicated that there are auspicious times and days e.g., Friday, known as sayyid al-ayyām (leader of the days). The determination of auspicious days in marriage has been adjusted to follow social changes, government policies, and Islamic laws, especially ‘urf and maslahah. Such a custom can be categorized as ‘urf shahih (good) and not 'urf fasid(deviating), with the values of public interest being for safety and blessing. The argument of this study is that in the context of Islamic law if the determination of the auspicious day does not deviate from the provisions of Islamic law, it can be accommodated as a legal consideration; yet, if it deviates from Islamic law, guidance is necessary. This is in accordance with the rules of fiqh: “preserving old things that bring benefits, and accommodating new things that are more beneficial.”